The Impact Of Coal And Nickel Shocks On Stock Volatility Throughout The Dynamic Era - Laksono, Gunadi; Putri, Anindya Prasisca Rena Zhetira (KEUNIS, 2024)
Numerous scholars have examined the relationship between stock returns and metal commodities, but there has been less emphasis on specific metal commodities such as coal and nickel. This study sought to investigate the correlation between coal and nickel price fluctuations and their impact on stock market volatility. The researchers employed the GARCH and EGARCH models for analysis. This study utilized data on coal price, nickel price, and two stock market indices in Indonesia, specifically LQ45 and IDX30, spanning from January 2020 to December 2023. The results indicate that there was no substantial correlation between coal shock and nickel shock on stock market volatility. The EGARCH model would be more suitable for prediction. The significance of this research lies in its discovery of the relationship between coal shock and nickel shock on stock return throughout a dynamic period.